Pengaruh Perbedaan Jenis Pakan Terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Lele Dumbo (Clarias gariepenus) - Wahyudi, Agus; Julyantoro, Pande Gde Sasmita; Kartika, I Wayan Darya (Current Trends in Aquatic Science, 2021)
Feed is an important component in catfish farming activities. The feed cost can reach about 60-70% of the total production cost. This study aims to determine the effect of different types of feed on the growth and survival of African catfish (Clarias gariepinus) seeds. This research was conducted in June 2019 until July 2019 at Banyuwangi Kabat Fish Seed Center. This research was use experimental method by a Completely Randomized Design (CRD) consisting of three treatments and three replications, namely treatment A using silkworm feed (Tubifex sp.), Treatment B using frozen Daphnia sp., and C treatment using artificial crumble (PF-800) feed. The results showed that treatment A gave an absolute weight growth of 1,22 ± 0,14 grams, absolute length 4,41 ± 0,14 cm, SR value of 100 ± 0% and FCR 1,4, while treatment B gave an absolute weight of 0,94 ± 0,13 gram, absolute length 1,55 ± 0,22 cm, SR value of 100 ± 0%, FCR 1,8, and C treatment resulted in absolute weight of 0,97 ± 0,03 grams, absolute length of 2,83 ± 0,05 cm, SR value of 90 ± 10%, and FCR value of 1,6 The water quality parameters in each treatment namely temperatures ranged 26,5 0 C-27,5°C, pH ranges 7,40-7,45, DO (Dissolved Oxygen) around 5,51-5,53 ppm, and ammonia values 0,78-2,72 ppm. Overall the measured water quality values are within the optimum range to support the growth of catfish seeds.